Postoperative hypothermia in geriatric patients undergoing arthroscopic shoulder surgery - Chun, Eun Hee; Lee, Guie Yong; Kim, Chi Hyo (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: Hypothermia below 36°C is a common problem during arthroscopic shoulder surgery. Geriatric patients are more vulnerable to perioperative hypothermia. The present study compared postoperative hypothermia between geriatric and young adult patients receiving arthroscopic shoulder surgery. Methods: Data were collected retrospectively from a geriatric group (aged 65 or more, n = 29), and a control group (aged 19–64, n = 33) using the anesthesia records of patients who had undergone arthroscopic shoulder surgery. The primary outcome measure was the incidence of hypothermia upon arrival in the postanesthesia care unit (PACU). The secondary outcome measure was the decrease in body temperature from admission into the operating room to admission into the PACU. Results: The incidence of hypothermia was 93.1% and 54.5% in the geriatric and control groups, respectively, demonstrating a significant difference between the groups (P < 0.001). Comparison between body temperature revealed a decrease of 1.5 ± 0.6°C and 1.0 ± 0.4°C in the geriatric and control groups, respectively, showing a significant difference between the groups (P < 0.001). The degree of hypothermia was significantly different between the groups (P = 0.027). No shivering was observed in either of the two groups, but the incidence of thermal discomfort was higher in the geriatric group than in the control group (P = 0.021). Conclusions: In geriatric patients undergoing arthroscopic shoulder surgery, both the incidence of postoperative hypothermia and the associated temperature drop are more prominent than those in young adult patients. Additional warming methods will be needed to prevent postoperative hypothermia in geriatric patients. KCI Citation Count: 1